The Analysis of Instrument of The Ability to Acting and Thinking Creatively Based Rasch Model - Suraji, Suraji; Sumaryanto, F.L, Totok; Khumaedi, Muhammad (Universitas Negeri Semarang, 2019)
The development of student’s creativity was to answer the challenges of the 21st century curriculum. To know the aims of learning were reached, it was needed valid and reliable assesment. Research was conducted instrument development. The total sample testing instrument need 43 students from two schools who have used 2013 curriculum. Rater reliability data analysis using Hoyt’s formula with SPSS software application . Validity and reliability items analyzed using Rasch model with Winstep program. Results: The 22th items tried out form 2 dimensions factor, they were namely the figural and verbal factors. Conclusion: results from test run on reliability was 0,94. The instrument based on the catagories was of good quality item. Based on the analysis factor it was will necessary to do improvement toward the arrangement of measuring instruments. The instrument consisted of two dimensions of the main dimensions which were figural and verbal dimension. Figural dimension had 10 measuring items, while verbal dimension had 12 measuring items. Instrument was arranged based on the lowest to highest logit. Sugestion: it required test run using larger sample. Items was arranged rom the easiest to hardest items based on logit number on each dimension. The benefits of this study: to arrange the model formula to assess the ability of acting and thinking creatively based on comic in the learning.